Analysis of Groundwater Potential in the Coastal Area of Parangtritis using Geoelectrical VES Method - La Ode Saleh Isa; Tjahyo Nugroho Adji; Ignasius L. Setyawan Purnama (Media Komunikasi Geografi, 2022)
This research was conducted in the coastal area of Parangtritis, Bantul Regency, Special Region of Yogyakarta. This study aims to describe the hydrostratigraphy of aquifers using the Vertical Electrical Sounding (VES) geoelectric method, to calculate the volume of availability and safe yield of groundwater application, and to compare the volume of availability of safe products with the demand for water for domestic and tourism purposes. This study uses a field survey approach and field data analysis. In this study, there were 9 VES measurement points for primary data and 16 VES measurement points from secondary data, five samples of water demand for restaurants, and 74 samples of domestic groundwater needs. The VES point was measured by a purposive random sampling method representing each landform. Hydrostratigraphic analysis and preparation of 2D and 3D cross-sectional models of subsurface lithology were performed on all VES geoelectrical measurement data. The results showed that the aquifer layer is located at varying depths for each landform, with alluvium sand as the constituent material. The most significant potential for groundwater is found in the form of dunes and beach ridges. The second-largest groundwater potential is in fluviomarine landforms, and the most minor is in the alluvial plain. The groundwater availability in each landform is sand dune and beach ridge of 117,776,100 m3; fluviomarine plain (45,422,700) m3; and alluvial plain (25,553,000) m3. Then, the safe yield of groundwater is 3,498,300 m3 in sand dunes and beach ridges, fluviomarine plain (1,566,300 m3), and alluvial plains (580,750 m3). Meanwhile, based on the calculation of the total need for groundwater for domestic and tourism purposes, the availability of safe yield is still in surplus or sufficient for the estimated needs.